Scarring and selection in the Great Irish Famine - Matthias Blum; Christopher L. Colvin; Eoin McLaughlin (Queen's University Centre for Economic History (QUCEH), 2017)
What impact do famines have on survivors? We use individual-level data on a population exposed to severe famine conditions during infancy to document two opposing effects. The first: exposure to insufficient food and a worsened disease environment is associated with poor health into adulthood - a scarring effect. The second: famine survivors do not themselves suffer any health impact - a selection effect. Anthropometric evidence from records pertaining to over 21,000 subjects born before, during and after the Great Irish Famine (1845-52), one of modern history's most severe famine episodes, suggests that selection is strongest where famine mortality is highest. Individuals born in heavily-affected areas experienced no measurable stunted growth, while significant scarring was found only among those born in regions where the same famine did not result in any excess mortality.
Keywords: I15; I32; N33; Q54; 330; famine; fetal origins hypothesis; anthropometrics; economic history; Ireland